Museums, gender and Wikipedia: postcustodial perspectives of Information Science - Silva, Stephanie Cerqueira [UNESP]; Macena, Isabela Correa [UNESP]; Jorente, Maria Jose Vicentini [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2025)
Collaborative environments on the Web, such as Wikipedia, are configured as spaces of participatory culture that reflect social dimensions. Through their themes and gender gaps, they emphasize the confluence with the agendas of women's museums, which provide opportunities for sharing, accessing, and preserving women's memories. In this sense, Information Science, in its post-custodial paradigm, offers a theoretical framework to develop strategies whose application integrates information and the social. Thus, the objective of this article is to analyze the Wikipedia platform as a potential collaborative resource for the visibility of women's museums. The research is descriptive-exploratory in nature, qualitative-quantitative, structured by a literature review and the phases of the Design Thinking methodology (inspiration, ideation, and implementation), based on a universe of 155 women's museums. The results demonstrated that the interrelation between women's museums and Wikipedia is capable of potentiating and giving visibility to the important theme of women's memory, as well as promoting discussions on contemporary sociocultural issues. Furthermore, it was evidenced that the post-custodial perspectives of Information Science are important concepts for digital-virtual strategies that involve sociocultural, technological, and scientific characteristics. It is concluded that there are ways to expand the visibility of women's museums, through proposals that use Wikipedia as a resource for accessing and sharing information, as well as for community participation. Therefore, various aspects of women's memory can be incorporated into the planning of information and communication processes, aiming at their importance in contemporary sociocultural issues.
Keywords: women's museums; gender; post-custodial paradigma; Wikipedia; technology and information